Pengembangan Media Pembelajaran Pop Up Book Digital Pada Materi Keberagaman Budaya Indonesia Kelas IV SDN Kenitenn1 - lailatun_nimah30* (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
This research is motivated by the low learning outcomes of fourth-grade students at SDN Keniten 1 on the topic of Indonesian cultural diversity, which is caused by the lack of concentration and student engagement during learning and the limited use of interactive learning media. This research aims to develop a valid, practical, and effective digital pop-up book learning media to improve student learning outcomes on the topic. This research uses the Research and Development (R&D) method with the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fourth-grade students at SDN Keniten 1. Data collection techniques include observation, interviews, questionnaires, and tests. The results showed that the media obtained a validity level of 78% from media experts with a feasible category and 94% from material experts with a very feasible category. The practicality level obtained was 96% from teachers, 88.75% in limited tests, and 96.87% in broad tests with a very practical category. The effectiveness of this media was demonstrated by a classical learning completion rate of 87.5% on the limited test and 87.5% on the broad test, as well as an average N-Gain of 0.72 on the limited test and 0.77 on the broad test, which is categorized as moderate to high. Thus, the digital pop-up book learning media was declared valid, practical, and effective in improving the learning outcomes of fourth-grade elementary school students in the subject of Indonesian Cultural Diversity.